MANAJEMEN STRATEGI PENGEMBANGAN OBJEK WISATA SEJARAH BENTENG TUANKU TAMBUSAI OLEH DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN ROKAN HULU - Rizki Anggraini; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The strategy management of historical tourist attraction development of Tuanku Tambusai Fortis important to be done because the tourist attraction of Tuanku Tambusai Fort possesses highhistorical value. Nevertheless, the conduction of strategy management of historical touristattraction development of Tuanku Tambusai Fort was still not optimally done. The concepttheory used in this research was the management strategy by Fred R. David (2011), byimplementing the indicator organizing, motivation, and staff replacement and factors influencedthe strategy management of tourist attraction development of Tuanku Tambusai Fort. This is aqualittive research with descriptive method. The technique of collecting data was conductedthrough interview, documentation, and observation. By using key informan as informationresourch and by using triangulation technique as a sourch of data validation. The researchfinding of this, the strategy management of historical tourist attraction development of TuankuTambusai Fort by Department of Tourism and Culture Rokan Hulu District was not optimal yet.This was suitable with the indicator implementation of strategy management that includesorganizers, motivation, staf replacement and factors affecting strategy management; they areresource, coordination, people participation, and unclear status of authority.Keywords: Strategy Management, Development, History Tourist Attraction